The dynamics of wealth, profit and sustainable advantage - Michael G. Jacobides; Sidney G. Winter; Stefan M. Kassberger (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
This paper shows how idiosyncratic resources can be the basis of sustained profitability and persistent heterogeneity under competitive conditions: Generic inputs purchased in the market become idiosyncratic resources by investments in customization. Analytically, we show how heterogeneous firms co-exist in equilibrium. Computationally, we show that sustainable profits can emerge without monopolistic imperfections. We consider how capability heterogeneity, resource customization cost and ease of expansion interact to drive short-run and sustainable profits. Results illustrate that, in an industry evolution context, sustainable profits may represent a small part of total wealth creation, and that changes in factors shaping a sectors' evolutionary trajectory may be more important than changes in factors that determine profits' ultimate sustainability, thus calling into question the familiar emphasis on sustainable advantage.
Keywords: 330; competitive advantage; sustainability; heterogeneity; industry evolution; rent appropriation